1957
DOI: 10.1111/j.1365-3059.1957.tb00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Wireworm and Slug Damage to Ware Potatoes, 1954–56

Abstract: Each autumn since 1947, the Potato Marketing Board (Potato Division of the Ministry of Food before 1955) has carried out a survey of maincrop potato growers in order to obtain good, pre-harvest estimates of ware production. Fields surveyed were, in general, on the same farms each year, and the original farm sample was selected to be as representative as possible of potato crops in each region of Great Britain having regard to variety, soil type, and potato acreage. Growers of less than one acre of potatoes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1961
1961
1974
1974

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…These results suggest that treatment was applied in a rather haphazard manner which bore little relation to the wireworm status of the individual fields. There is evidence, both from this country (Bevan and Bryden, 1956;Baker and Waines. 1957;MaskeU, 1958), and Canada (Burrage, 1960;Fox and Smeltzer, 1959), that soil treatments seldom eliminate damage, and are not very eflSdent at low wireworm population densities, in the season of application.…”
Section: Tuber Damage and Use Of Insecticidesmentioning
confidence: 83%
See 1 more Smart Citation
“…These results suggest that treatment was applied in a rather haphazard manner which bore little relation to the wireworm status of the individual fields. There is evidence, both from this country (Bevan and Bryden, 1956;Baker and Waines. 1957;MaskeU, 1958), and Canada (Burrage, 1960;Fox and Smeltzer, 1959), that soil treatments seldom eliminate damage, and are not very eflSdent at low wireworm population densities, in the season of application.…”
Section: Tuber Damage and Use Of Insecticidesmentioning
confidence: 83%
“…
A SUMMARY of results from a survey of pest damage to the ware potato crop over the years 1954-56 has already been published (Baker and Waines, 1957). The present article covers the seven-year period 1954-60, and is restricted to a consideration of wireworm damage in England and Wales in relation to the use of soil insecticides.
…”
mentioning
confidence: 99%
“…Baker & Waines 1957) and Stephenson (1965) showed that severe damage is likely where crops are irrigated. Baker & Waines 1957) and Stephenson (1965) showed that severe damage is likely where crops are irrigated.…”
Section: Introductionmentioning
confidence: 99%
“…
A SUMMARY of wirewomi and slug damage to ware potato crops in Great Britain for the years 1954to 1956(Baker and Waines, 1957) and a paper on wireworm damage to the ware potato crop in England and Wales, 1954 to 1960 (Strickland, Bardner and Waines, 1962 have already been published. In this paper, damage to potato crops in Scotland by wireworms and other soil pests (mainly slugs) is considered for the years 1954 to 1960.
…”
mentioning
confidence: 99%